The Role of Parents in Forming Children's Independence - Maria Hidayanti; Lita Lita; Mubiar Agustin (Journal of Education For Sustainable Innovation, 2023)
Independence is an essential aspect that needs to be instilled in children. Independence becomes a desired goal for every parent, especially as their children enter the school phase. Therefore, parents should provide opportunities for their children to grow and develop, enabling them to cultivate independence effectively. This research aims to investigate the role of parents in shaping children's independence. The study employs a qualitative descriptive method, with the subjects consisting of five children attending RA Siti Khodijah Majalengka. The research was conducted in February 2023. Data were collected through interview, observation, and documentation techniques. The research findings highlight the crucial role of parents in fostering children's independence. Parents must provide opportunities and room for their children to continuously learn about independence, while also consistently motivating and reminding students to be self-reliant, avoid dependency on others, and be capable of self-direction in the future. Throughout the process of cultivating independence, parental consistency and patience are vital, encompassing every phase and aspect of developing independence in children aged 5-6 years at RA Siti Khodijah Majalengka. The implementation of stimulation through habitual practices in shaping the independence of 5-6-year-old children at RA Siti Khodijah Majalengka is carried out through several school programs or activities, and this can be extended to the home environment or wherever the child is situated, specifically through life skills. Notably, activities conducted at school have a significant impact on fostering independence in children. Children are consistently provided with motivation, stimuli, and positive habits, repeated on a regular basis within the school setting.